DESCRIPTIVE STUDY OF STUDENTS’ MOTIVATION AND PERCEIVED GRAMMAR IMPROVEMENT THROUGH GAME-BASED LEARNING - Engelina Salainti; Allan Hubert Frederick Sanger (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2025)
This study examines the impact of game-based learning on students' interest and their perceptions of improving their grammar skills. The research involved students who took grammar lessons that included fun and interactive games meant to help them learn better. The study used descriptive analysis to find the mean and standard deviation from questionnaires, where students assessed their own grammar skills and how motivated they felt. The findings show that using games in class greatly increases students' motivation and helps them see their progress in grammar. The results suggest that using game-based learning is an effective way to teach grammar and get students more involved. The study also talks about what teachers can do in their classrooms and what future research could look into.